Projeto de Centro de Apoio e hospedagem sustentável para turistas na ilha do Combu em Belém - PA - AQUINO, Juliana Monteiro de (2023)
Sustainability has come into focus in all sectors of contemporary society. It seeks to combine economic and social development with respect for nature, aiming to preserve natural resources for future generations. Architecture projects and their execution are included in this context and perhaps, it is one of the main activities that could enable the achievement of a more sustainable world, its responsibility in the consumption of materials, the use of constructive techniques that use less resources and the creation of solutions that enable the reduction of energy consumption. Concomitantly, with international awareness of the threats that predatory exploration of resources would bring to nature, ecotourism arises. A new form of leisure tourism that takes tourists to visit places in search of an experience with nature in its purest state. This work seeks to contribute with a proposal for the creation of an architectural project, combining the best practices of the sustainable architecture and the potential of a new way of exploring the tourist activity in the island of Combu, in order to insert in the process of economic development, the riverside communities and the preservation of the environment.